Subjects of Cassation Appeal - Dilbandyan , S.; Sujyan , T. (Bulletin of Yerevan University C: Jurisprudence, 2017)
Subjects of Cassation Appeal.–General and special preconditions to exercise the right to appeal are analyzed in the article presented. The article definishiates the models of performance of the right to cassation appeal. In the light of the legal positions of the Constitutional Court and the European Court the article reveals the legitimacy of the requirement to file a complaint through a lawyer and the conclusion is made that such a regulation is necessary for the effective implementation of the right to a cassation appeal in case of clarification of legal assistance procedures at this stage. The author also analyzes the legitimacy of the requirement to file a cassation appeal only by the Prosecutor General or his deputy.
Keywords: special preconditions, general preconditions, models of performance of the right to cassation appeal, intermediary procedure of filing a complaint, accredited advocate, a lawyer with a special license